The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.ipm.2006.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Connection and stratification in research collaboration: An analysis of the COLLNET network

Abstract: The co-authorship network of scientists represents a prototype of social networks. By mapping the graph containing all relevant publications of members in an international collaboration network: COLLNET, we infer the structural mechanisms that govern the topology of this social system. Structure of the network effect not only individual's collaboration pattern deeply, but knowledge flowing process profoundly. However, a single view is not enough to grasp the characters of the network in details. We have to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 25 publications
4
88
0
2
Order By: Relevance
“…Commonly used measures are diameter, mean distance, components, clusters, etc. Micro-level metrics relate to the analysis of the individual properties of network actors, for example, actor position, actor status, and distance to others, which informs us about ''the differential constraints and opportunities facing individual actors which shape their social behavior'' (Yin et al 2006(Yin et al , p. 1600. It zooms in to capture the features of the individual nodes/actors in a network with the consideration of the topology of the network.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used measures are diameter, mean distance, components, clusters, etc. Micro-level metrics relate to the analysis of the individual properties of network actors, for example, actor position, actor status, and distance to others, which informs us about ''the differential constraints and opportunities facing individual actors which shape their social behavior'' (Yin et al 2006(Yin et al , p. 1600. It zooms in to capture the features of the individual nodes/actors in a network with the consideration of the topology of the network.…”
Section: Methodsmentioning
confidence: 99%
“…Newman studied and compared the coauthorship graph of arXiv, Medline, SPIRES, and NCSTRL (Newman 2001a, b) and found a number of network differences between experimental and theoretical disciplines. By mapping the graph containing all relevant publications of members in an international collaboration network COLLNET, Yin et al (2006) found that this scientific community displays many aspects of a small-world network and is vulnerable to disruption. Using the Science Citation Index (SCI) data for 1990 and 2000, Wagner and Leydesdorff (2003) found that in the 10 years between 1990 and 2000, the global network has expanded to include more nations and it has become more interconnected.…”
Section: Related Workmentioning
confidence: 99%
“…measures (Liu et al, 2005;Yin, Kretschmer, Hanneman, & Liu, 2006). The centrality measures the position of each vertex in the network, and directly associates with theories in social sciences as such "weak ties" and "social capital".…”
Section: Notesmentioning
confidence: 99%
“…Newman studied a variety of properties of his networks, including scientists' degree and betweenness [NEWMAN, 2001A,B]. Some studies have directly applied the degree, closeness and betweenness to co-authorship networks of different domains [YIN & AL., 2006;HOU & AL., 2008]. In addition to authors' degree, closeness, betweenness and PageRank centrality, the AuthorRank centrality of authors in the domain of digital libraries was proposed [LIU & AL., 2005].…”
Section: Related Workmentioning
confidence: 99%